Policy Brief: Sistem Asuh Siswa sebagai Strategi Pencegahan Bullying dan Penguatan Iklim Sekolah - Masduki Asbari; Wakhida Nurhayati; Danish Akbar Firdausy Asbari (Yayasan Aya Sophia Indonesia, 2026)
Bullying remains a pervasive problem in junior high schools worldwide, with documented negative consequences for students’ mental health, academic achievement, and school climate. Traditional disciplinary approaches have shown limited effectiveness, creating a policy gap in preventive, relationship-based interventions. This study presents a policy-oriented case analysis of a peer mentoring system—locally termed the “student guardianship system” (sistem asuh antar siswa)—implemented at SMP Aya Sophia Islamic School as a low-cost, integrated governance strategy to prevent bullying and strengthen school climate through familial relationships. Using qualitative policy-oriented methodology, the research collected data through document analysis, semi-structured interviews with school leaders and teachers, and observational implementation notes. Findings reveal that the system operates through a hierarchical structure pairing older students as mentors (“kakak asuh”) with younger cohorts, embedded within formal school governance, supported by regular facilitation meetings and aligned counseling services. The mechanism prevents bullying through structural monitoring, creates psychological belonging and safety, and activates peer support networks. Teachers and administrators report measurable improvements in student risk-taking behavior reduction, enhanced school connectedness, and improved academic engagement—effects consistent with peer mentoring and school climate literature. The study’s novelty lies in demonstrating how faith-based institutional values (nilai kekeluargaan, family-centered values) can operationalize peer mentoring at scale within existing school structures, addressing both prevention and governance simultaneously. Implementability is high: the system requires minimal external resources, aligns with Islamic educational principles, and is readily replicable in comparable school contexts. Recommendations address formal institutionalization through school standard procedures (SOP), mentoring training protocols, and periodic monitoring frameworks.